Little quick fix: Plan your research project - Trivedy, Kelly; Owen, Alysha (New Delhi: Sage Publications, 2021)
Guiding you through how to plan your research project, this Little Quick Fix covers everything from how to get started and the stages of research, to avoiding procrastination and staying on track. Like other books in the Little Quick Fix series, this book provides a stand-in for the busy or unavailable supervisor when students are really stuck.
includes bibliographical references.
Keywords: RESEARCH; ACADEMIC WRITING; RESEARCH DESIGN; ÉCRITURE SAVANTE; handbooks; Handbooks and manuals; Handbooks and manuals; Guides et manuels